The impact of ICT penetration on deforestation: A panel data evidence - Rasim Yılmaz; Cuneyt Koyuncu (Review of Economic Perspectives, 2019)
A growing number of case studies and reports suggest that Information and Communication Technologies (ICT) play an important role in fighting against deforestation, and the penetration of ICT help decrease deforestation in a different part of world's forests. The aim of this study is to test whether diffusion of ICT contributes to decreasing in deforestation in the world. For this purpose, the effect of ICT penetration on deforestation is estimated by using bivariate and multivariate fixed time effect models. In the sample selection process, those countries having 2% or more forest area as a percentage of total land area we included in our analysis. The largest sample includes 174 countries. The period under study is between 1991 and 2012. It is found that ICT penetration is significantly and negatively associated with deforestation. The results are robust to the inclusion of a number of control variables as well as different indicators of ICT penetration and deforestation as such all available four ICT indicators and two deforestation indicators are used. To avoid potential spurious regression problems in the analyses, the original models are re-estimated by using the stationary forms of all independent and dependent variables. A strong negative correlation between ICT indicators and deforestation indicators is also supported by the findings of re-estimated bivariate and multivariate models. Empirical evidence at the macro level provided in this paper confirms the results mentioned in the case studies.
Keywords: Q23; Q56; O33; C23; 330; Deforestation; Forest Management; Information and Communication Technologies; Panel Study